Stretched Horizon as a Quantum Gravity Beam Splitter - Crowell, Lawrence (Frontiers in Physics, 2022)
The disentanglement of a black hole with its Hawking radiation is a form of CNOT operation that demolishes entanglements [1]. This mechanism is due to boundary condition set up on the stretched horizon in holography [2]. This is reconsidered here as an entanglement swap with the transfer of entanglement, where aged Hawking radiation is not entangled with the black hole, but rather with gravitons or BMS charges at I+